Analisis Metode Demonstrasi pada Pelajaran Bahasa Indonesia dalam Meningkatkan Keterampilan Membaca Puisi Siswa Kelas IV - Syarif, Ahmad; Suryana, Agus; Tanjung, Ira Nur Mutiara; Rahmawati, Nopi; Mariamah, Siti; Aji, Wiyarsih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to analyze the learning process using the demonstration method in improving the poetry reading ability of grade IV students in the second semester of the 2023/2024 academic year. The data collection method uses the literature method, namely literature research. The data collection technique is carried out, by listing all the variables that need to be researched, namely: learning implementation, demonstration methods, poetry reading skills material. Select the necessary descriptive materials from available sources such as books, articles or biographies that are relevant to the problem being studied. From this study, it can be concluded that the application of the demonstration method in learning Indonesian can improve students' poetry reading skills, with an implementation process consisting of three stages: 1) demonstration method learning strategy, 2) implementation of learning with demonstration method, 3) evaluation of the learning process and learning outcomes using the demonstration method.